Rehabilitation of degraded tropical forestry ecosystems - Centro para la Investigación Forestal Internacional (CIFOR) (1999)
Project: Rehabilitatiton methods in second-growth forest and degraded lands in the Ucayali region, of the Peruvian Amazon.